1995
DOI: 10.1038/bjc.1995.526
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin blocks the stimulatory effects of prolactin on human breast cancer cell growth in culture

Abstract: Summary Melatonin (aMT) appears to be a potentially important oncostatic substance that can block the mitogenic effects of tumour-promoting hormones and growth factors such as oestradiol and epidermal growth factor, in vitro. In the present study, we examined the possibility that aMT would also inhibit the stimulatory effects of the tumour-promoter prolactin (PRL) on MCF-7 and ZR75-1 human breast cancer cell (HBC) growth under 5% charcoal-stripped fetal bovine serum culture conditions. Human PRL (10-100ng ml-'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 24 publications
2
13
0
3
Order By: Relevance
“…Melatonin shows antigonadotropic and antioestrogenic actions in different study module, in vitro and in vivo on hormone-dependent tumours and cancer cell line [44] as well as antagonised the action of prolactin on human breast cancer cell (HBC) [54]. It selectively neutralised the effects of estrogens on the breast and the local biosynthesis of estrogens from androgens [55].…”
mentioning
confidence: 99%
“…Melatonin shows antigonadotropic and antioestrogenic actions in different study module, in vitro and in vivo on hormone-dependent tumours and cancer cell line [44] as well as antagonised the action of prolactin on human breast cancer cell (HBC) [54]. It selectively neutralised the effects of estrogens on the breast and the local biosynthesis of estrogens from androgens [55].…”
mentioning
confidence: 99%
“…Furthermore, melatonin was shown to lose its antimitogenic properties in serum-free medium unless cells are also simultaneously exposed to estradiol [92], epidermal growth factor [93] or prolactin [94].…”
Section: Oncostatic Role Of Melatoninmentioning
confidence: 99%
“…Although some recent studies have reported melatonin oncostatic activity in human breast cancer cell lines in vitro [93], very little is known about the clinical use of melatonin in breast cancer patients [94]. In a similar manner, the evidence for a role of melatonin in the management of patients with metastatic solid tumors remains insufficient.…”
Section: Melatonin the Immune System And Cancermentioning
confidence: 98%